2018
DOI: 10.2196/11007
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages and Disadvantages of Online and Blended Therapy: Survey Study Amongst Licensed Psychotherapists in Austria

Abstract: BackgroundWeb-based and blended (face-to-face plus Web-based) interventions for mental health disorders are gaining significance. However, many licensed psychotherapists still have guarded attitudes toward computer-assisted therapy, hindering dissemination efforts.ObjectiveThe objective of this study was to provide a therapist-oriented evaluation of Web-based and blended therapies and identify commonalities and differences in attitudes toward both formats. Furthermore, it aimed to test the impact of an informa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
99
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 51 publications
15
99
0
20
Order By: Relevance
“…The notion that technology in the form of multimedia might be useful for psychoeducation, expressed in the psychoeducational value factor in the present work, has also been previously reported in qualitative studies (Stallard et al, 2010; van der Vaart et al, 2014). Finally, the perceived relevance factor in this study might be comparable to Relative advantage subscale in Carper et al's study (2013) or to the concept of effort expectancy within the theoretical framework of Unified theory of acceptance and use of technology (UTAUT; Venkatesh, Morris, Davis, & Davis, 2003) investigated in other work (Schuster et al, 2018). Based on the small to medium correlation between this factor and the potential to augment factor, it appears that, while psychotherapists may believe that these innovative treatments have some added value, they can still find them not worth the effort.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The notion that technology in the form of multimedia might be useful for psychoeducation, expressed in the psychoeducational value factor in the present work, has also been previously reported in qualitative studies (Stallard et al, 2010; van der Vaart et al, 2014). Finally, the perceived relevance factor in this study might be comparable to Relative advantage subscale in Carper et al's study (2013) or to the concept of effort expectancy within the theoretical framework of Unified theory of acceptance and use of technology (UTAUT; Venkatesh, Morris, Davis, & Davis, 2003) investigated in other work (Schuster et al, 2018). Based on the small to medium correlation between this factor and the potential to augment factor, it appears that, while psychotherapists may believe that these innovative treatments have some added value, they can still find them not worth the effort.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have shown that psychotherapists hold neutral to positive attitudes toward these forms of treatment (Becker & Jensen‐Doss, 2013; Schuster, Pokorny, Topooco, Berger, & Laireiter, 2018; Vigerland et al, 2014), while some studies imply that psychotherapists might be less enthusiastic than patients in light of concerns about their effectiveness and patient adherence (Newton & Sundin, 2016; Schröder et al, 2017; Whitfield & Williams, 2004). Valuable information has been gained through qualitative studies and surveys (Gun et al, 2011; Newton & Sundin, 2016; Schuster et al, 2018; van der Vaart et al, 2014). However, valid instruments are still needed for examining psychotherapists' attitudes towards technology use in psychotherapy more reliably and exploring the relationship between these attitudes and psychotherapist behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Jedoch haben Psychothe rapeutinnen und therapeuten Vorbehalte gegenüber der thera peutischen Nutzung von Neuen Medien. Diese liegen u. a. in nicht eindeutig geregelten zeitlichen Vorgaben und Vergütungen des Medieneinsatzes [3,7], technischen Schwierigkeiten [8] oder Sor gen um den Datenschutz [9]. Zudem besitzt ein großer Anteil der Psychotherapeuten kein oder nur ein geringes Wissen über Blen ded Therapy Ansätze, bspw.…”
Section: Introductionunclassified
“…Lastly, many therapists lack experience with this novel approach and hold more cautious attitudes towards online interventions [16]. Comparable levels of caution and awareness have been found amongst different interest parties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…****************** Figure 1 about here *********************** According to therapists, patients can profit from blended interventions in form of increased treatment accessibility and flexibility, as well as from the improvement of patients' selfmanagement and the optimal use of face-to-face sessions [31,32]. Additionally, mental health care providers, policy makers and other such organisations seem to have a more positive conception of blended therapy compared to pure online therapy [17], and therapists seem to prefer the blended format because it is associated with less risks [16]. Amongst the potential disadvantages of the integrated format, therapists frequently remark that blended therapy is not feasible for all patients, and that the format at times could hamper the therapeutic process -in particular the establishment of the therapeutic alliance [31,32].…”
Section: Introductionmentioning
confidence: 99%